(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The article discusses the phenomena of construction of a new identity for the Ottoman Muslim woman in the second half of the I 9th century. The analysis is focused on the first attempts toward emancipation of the women from the Ottoman elite. A special interest is provided to the initiator of Turkish women's movement, the novelist Fatima Aliye.